Targeting Multiple Aminoacyl-tRNA Synthetases Overcomes the Resistance Liabilities Associated with Antibacterial Inhibitors Acting on a Single Such Enzyme - Randall, Christopher P.; Rasina, Dace; Jirgensons, Aigars; O'Neill, Alex J. (Antimicrobial agents and chemotherapy, 2016)
Bacterial aminoacyl-tRNA synthetases (aaRSs) represent promising antibacterial drug targets. Unfortunately, the aaRS inhibitors that have to date reached clinical trials are subject to rapid resistance development through mutation, a phenomenon that limits their potential clinical utility. Here, we confirm the intuitively correct idea that simultaneous targeting of two different aaRS enzymes prevents the emergence of spontaneous bacterial resistance at high frequency, a finding that supports the development of multitargeted anti-aaRS therapies.